2018
DOI: 10.1039/c8ra07192f
|View full text |Cite
|
Sign up to set email alerts
|

Selective enrichment of sialylated glycopeptides with a d-allose@SiO2 matrix

Abstract: Abnormal sialylation of glycoprotein is associated with different kinds of cancers and neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…In another study, identical results were obtained with Sepharose, PGC and dextran‐bonded silica for the separation of complex N ‐glycans (Chen, Ding, et al, 2018). Sun, Xiong, et al (2018) have developed a D‐allose@SiO 2 matrix and found that enrichment of sialylated glycopeptides was notably higher than with the commercially available Sepharose CL‐6B or TiO 2 resins.…”
Section: Studies On Specific Carbohydrate Typesmentioning
confidence: 99%
“…In another study, identical results were obtained with Sepharose, PGC and dextran‐bonded silica for the separation of complex N ‐glycans (Chen, Ding, et al, 2018). Sun, Xiong, et al (2018) have developed a D‐allose@SiO 2 matrix and found that enrichment of sialylated glycopeptides was notably higher than with the commercially available Sepharose CL‐6B or TiO 2 resins.…”
Section: Studies On Specific Carbohydrate Typesmentioning
confidence: 99%
“…Glycopeptide enrichment of tryptic digested fetuin and BSA (the molar ratio of fetuin to BSA is 1:100) using TiO 2 was performed according to the reported method [11,22,37].…”
Section: Enrichment Of Glycopeptides With Tiomentioning
confidence: 99%
“…The nonglycopeptides were not labeled in the mass spectra of a and c glycosylation groups of identified glycopeptides is presented in Table S1 (see ESM). For comparison, the commercial TiO 2 beads, which have also been used in the enrichment of SGPs via a multipoint binding, similar to a multidentate binding, between negatively charged sialic acid and TiO 2 [11,42], were employed to enrich glycopeptides from the mixtures of fetuin and BSA according to the reported extraction method [11,22,37]. As shown in Fig.…”
Section: Enrichment Performance Of Mpmf Materials To Sgpsmentioning
confidence: 99%
“…Although exhibiting high SGP enrichment selectivity, hydrazide chemistry-based methods lose the information of terminal SAs . Recently, various novel solid-phase materials have been developed to enrich SGPs exclusively, on account of in-depth interdisciplinarity and a joint force of materials science and analytical chemistry to solve problems. Among them, an interesting study demonstrated the unique advantage of dynamic covalent chemistry based on Schiff-base hydrolysis in capturing SGPs . Despite the excellent performance, the uniqueness of each material and complicated process for producing as well as characterizing them hindered their widespread applications in general analytical labs.…”
Section: Introductionmentioning
confidence: 99%